Work System Design in the Wallet Production Process Using the Full Time Equivalent (FTE) and Cardiovascular Load (CVL) Method - Misbaghi, Yoni Fajar; Putra, Boy Isma (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
UKM Gudang Dompet is a company that produces wallets. The number of orders will affect employee performance because the number of targets achieved will increase the workload for employees, causing fatigue. To prevent excessive fatigue felt by workers in the production division at the Dompet Warehouse, it is necessary to measure workload. The Full Time Equivalent (FTE) method measures working time, which is based on working time, measuring the time needed to complete a particular task and then converting it into an FTE index value. The cardiovascular load (CVL) method measures physical workload based on comparing pulses. Working pulse with a maximum pulse. This research showed that worker fatigue occurred in the packing section, indicated by a CVL value of more than 30%, so FTE calculations were carried out to determine energy consumption. Based on energy consumption calculations, the results obtained are an additional rest time of 32.85 minutes in the packing section. Keywords: workloads; full-time equivalent; CVL; work system design.